MENJELAJAHI EKOLOGI INTEGRAL DALAM PERSPEKTIF TEOLOGI KRISTEN: SEBUAH ANALISIS TERHADAP DOKTRIN PENCIPTAAN DAN KEUTUHAN MANUSIA : Ekoteologi Kristen - Yeunike; Chindy Kendenan Pareang; Auriel Risti Tappi'; Prionaray Bram (THEOLOGIA INSANI: Jurnal Theologia, Pendidikan, dan Misiologia Integratif, 2026)
This journal examines integral ecology in the context of Christian theology, focusing on an in-depth analysis of the doctrine of creation and the concept of human wholeness. Based on the interpretation of the Book of Genesis, humans are positioned not as dominant rulers, but as managers and stewards of God's creation, emphasizing moral responsibility for environmental preservation. The concept of human wholeness, which encompasses physical, psychological and spiritual dimensions, shows the intrinsic link between human well-being and ecosystem health. The global ecological crisis, characterized by exploitation of natural resources, climate change, and environmental injustice, demands theological reinterpretation and concrete action. This journal examines the implications of integral ecology for Christian theology, including reconciliation between humans and nature, lifestyle change, and the promotion of environmental justice. This research contributes to building a comprehensive Christian environmental ethic, integrating spirituality, social action, and commitment to sustainability.